Real-World Data on Access to Standards of Care for People With Spinal Muscular Atrophy in the UK - Muni-Lofra, Robert; Murphy, Lindsay B.; Adcock, Kate; Farrugia, Maria E.; Irwin, Joseph; Lilleker, James B.; McConville, John; Merrison, Andria; Parton, Matt; Ryburn, Liz; Scoto, Mariacristina; Marini-Bettolo, Chiara; et al. (Frontiers in Neurology, 2022)
Spinal Muscular Atrophy (SMA) is characterised by muscle atrophy and weakness and has an incidence of 1:11.000 live births which projects an estimated population in the UK of 650 to 1,300 affected patients. Standards of Care (SoC) were updated in 2017 and they have been widely adopted as a reference for implementation of care in SMA across the globe. The effectiveness of implementation and adherence to these standards across different countries is unclear. The aim of this study is to describe the experience of individuals with SMA regarding their care in the UK. An online anonymised survey was sent out via patient organisations, the UK SMA Patient Registry, professional networks, and social media to reach across the UK. The survey captured demographic profile, professionals involved in a patient’s care, Interventions and access to mobility aids and home adaptations. Participants responded about their access to services and to rate how important each professional and intervention was for their health and wellbeing. 128 responses were collected with a median age of 34 years (1–81). 73% of participants were adults and 60% men. Overall good access to neurologist (>90%) but limited to nurse specialist (48%) and physiotherapist (57%). Good access to respiratory support was reported but limited for interventions for positioning and bracing and exercise. This survey highlights that access to certain professionals for people with SMA is limited in the UK. Striking differences were noted between pediatric and adult populations. Limited access to care were regularly reported, with half of the study population consistently not accessing full multidisciplinary care. Access to interventions for contracture management were recorded to have significant limitations. Mobility aids and home adaptations are widely available and were also reported as the most valued interventions. Access to nutritional support or speech and language therapy appears only to be available for a small proportion of the participants. Access to respiratory care was good especially in severe forms of SMA. We found pockets of good practice in the UK that align with the SoC. However, access is not equal for adults and children and access to certain professionals is significantly limited.